Polyphenylene sulfide- expanded graphite nanocomposites: Processing route dependent electrical percolation. (December 2017) - Ramanujam, BTS; Radhakrishnan, S; Deshpande, SD
Polyphenylene sulfide (PPS)-expanded graphite (ExGr) conducting nanocomposites have been prepared by powder mixing and in situ polymerization routes after sonicating ExGr particles in acetone. Synthesized PPS has been used to make powder mixed composites. The powder mixed composites exhibit a percolation threshold of 3 wt% due to the formation of graphite nanosheets. When PPS-ExGr composites are prepared by in situ polymerization route, very low electrical percolation threshold less than 0.5 wt% ExGr is obtained. The low percolation threshold obtained is attributed to better dispersion of ExGr nanosheets in the polymer matrix when compared to powder mixed composites. The synthesized PPS has been characterized by X-ray diffraction, differential scanning calorimetry, and infrared spectroscopy. The formation of graphite nanosheets has been confirmed by transmission and scanning electron microcopy analysis.